Early Brain Injury or Cerebral Vasospasm Volume 1: Pathophysiology - Feng, Hua.; Mao, Ying.; Zhang, John H.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
More than 40 articles provide an extensive coverage of advances over the last three years of research on subarachnoid hemorrhage-induced brain injuries and cerebral vasospasm. Early brain injury, the new frontier of subarachnoid hemorrhage research, which may be a key contributor to the high mortality and morbidity, promotes collaborative efforts from neurosurgery, neurology, neuro-ICU into other interrelated fields and basic neurosciences. For the first time, subarachnoid hemorrhage research is almost equally divided by early brain injury and cerebral vasospasm, mechanistic investigations and therapeutic approaches, demonstrating a translational feature of the future direction.
Keywords: Medicine; Neurosurgery; Medicine & Public Health; Neurosurgery